Combining Essential Oils with Each Other and with Clotrimazole Prevents the Formation of Candida Biofilms and Eradicates Mature Biofilms - Rafael Alves da Silva; Nagela Bernadelli Sousa Silva; Carlos Henrique Gomes Martins; Regina Helena Pires; Denise Von Dolinger de Brito Röder; Reginaldo dos Santos Pedroso (MDPI AG, 2022)
Fungal infections by Candida spp. are opportunistic and most often occur in individuals with some predisposing factor. Essential oils (EO) have anti-Candida potential, being a therapeutic alternative to be explored, especially for superficial and mucosal candidiasis. The objective was to analyze the synergistic potential between the EO of Citrus limon, Cupressus sempervirens, Litsea cubeba and Melaleuca alternifolia, and each of them with clotrimazole, to inhibit in vitro the formation and eradication of Candida spp. biofilms. Added to this, the survival of Caenorhabditis elegans was evaluated after exposure to EO, clotrimazole and their synergistic combinations. Anti-Candida activity was determined by microdilution for the substances alone and in EO-EO and EO-clotrimazole combinations. The combinations were performed by the checkerboard method, and the reduction in the metabolic activity of biofilms was determined by the viability of MTT/menadione. C. elegans larvae survival was evaluated after 24 h of exposure to EO, clotrimazole and synergistic combinations. The minimum inhibitory concentration (MIC) of EO ranged from 500 to >4000 µg/mL. The lowest MIC (500 µg/mL) was for C. sempervirens and L. cubeba on a C. krusei isolate; for clotrimazole, the MIC ranged from 0.015 to 0.5 µg/mL. Biofilm inhibition and eradication both ranged from 1000 to >4000 µg/mL. The lethal concentration (LC50) of C. limon, L. cubeba and M. alternifolia was 2000 µg/mL for C. elegans, while for C. sempervirens and clotrimazole, it was not determined within the concentration limits tested. In combination, more than 85% of the larvae survived M. alternifolia-clotrimazole, M. alternifolia-L. cubeba, C. sempervirens-clotrimazole and C. sempervirens-C. limon combinations. This study is the first, to our knowledge, to present a synergistic relationship of EO-EO and EO-clotrimazole combinations on Candida spp. biofilms.